(untitled) (Journal of Science and Technology, 2016)
Most farmers in sub-Saharan Africa use very little market inputs. Consequently output of the farm depends crucially on the size of the cultivated area each season. Moreover, larger farmers are known to be less risk averse and hence are more likely to adopt improved technologies. Thus the question of how farmers’ decisions about farm size are informed is very significant. Using farm-level data from Northern Ghana, this article demonstrates the significance of access to family and market labour, as well as functional markets for both inputs and outputs. In particular, it is concluded that farmers will not adopt mechanical equipment to expand cultivated surfaces unless there are complementary technologies to accomplish post-land preparation field operations that are currently not mechanised, or they have the ability to recruit additional labour to overcome labour bottlenecks.